CARACTERIZACIÓN HISTOLÓGICA DEL TIMO EN FETOS DE ALPACA - Montenegro B., Juan (2006)
The objective of the present study was to study the cytoarchitectural structure of the cervical and thoracic segments of thymus in alpaca (Lama pacos) fetuses. For this purpose, 10 fetuses between 40-190 days of gestation were collected form the local slaughterhouse. At day 40, the developing thymus has acinar cytoarchitectural morphology, infiltrated by a few lymphoid cells surrounded by mesenchymal cells. At day 60, the cervical segment looks like a «follicular» lymphoid, densely populated by thymocytes, whereas the thoracic region has a cystic appearance with short trabecular projections. Cortex and medulla differentiation starts in the posterior cervical and thoracic segments by day 100 and in the anterior cervical segments by day 130, and is well established by day 165. The thymic capsule remained as a double cellular layer of lax connective tissue. Subcapsular and trabecular blood vessels have fenestrated endothelium. Erythroblastic cells were observed by day 100 in the cortex and subcapsule zones. Medullar Hassall’s corpuscles were observed by day 100, and the epithelial reticular cell barrier in the cortical medullar zone was observed by day 130.